Pengaruh Teknologi Digital Terhadap Keputusan Pelanggan Dalam Memilih TekFin Pinjaman di Indonesia - Kurniasari, Florentina; Endarto, Eko Agus Prasetyo (Manajemen Bisnis Kompetensi, 2018)
Digital technology that is increasingly growing in Indonesia, characterized by an increase in the number of mobile phone users, has led to an increase in financial transactions carried out electronically by 24% in 2017. However, these developments are not in line with the level of financial inclusion of the Indonesian people, which only 64% of people have access to banks. This study aims to analyze the factors of digital technology that can influence customer decisions in using financial technology products (tekfin). The decision to use Tekfin services was influenced by how much customer knowledge was about Tekfin products. The sample in this study was MSME customers from the Rural Credit Bank (BPR) located in Central Java. Data is processed statistically using Structural Equation Method (SEM). The results showed that the customer’s decision in choosing Tekfin was strongly influenced by familiarity, level of literacy and knowledge possessed about Tekfin. Furthermore, this knowledge is formed by the existence of information communicated through social networks, the clarity of government regulations and the type and quality of financial services offered. This research emphasizes the need to provide information through education, intensive promotion supported by government protection so that tekfin users in Indonesia will grow. Keywords: Digital Technology, Customer Decisions, Financing Loans, BPR